2012
DOI: 10.1103/physrevlett.108.116802
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Induced Surface Metallization ofSrTiO3(001)

Abstract: Surface metallization of SrTiO3(001) by hydrogen adsorption is experimentally confirmed for the first time by photoemission spectroscopy and surface conductivity measurements. The metallic state is assigned to a quantized state in the space-charge layer induced by electron doping from hydrogen atoms. The measured two-dimensional (2D) conductivity is well above the 2D Ioffe-Regel limit indicating that the system is in a metallic conduction regime. The mean free path of the surface electron is estimated to be se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 31 publications
6
53
2
Order By: Relevance
“…18,19 In this study, we use first-principles calculations within density functional theory (DFT) 70 to investigate the energetics of hydrogenation on the MoS 2 monolayer and the resulting change in electronic properties with aim to explore the possibility of the surface metallization and the construction of conducting channels. Clearly the motivation to hydrogenate MoS 2 here is in stark contrast to that to hydrogenate graphene: hydrogenating graphene causes its band gap openinga metal to insulator transition-which can be used to create 5 insulating ribbons or clusters on graphene. 20,21 Our ballistic conductance calculation shows that hydrogenation-induced metallization is viable on MoS 2 monolayer and strip-patterned hydrogenation can generate a nanoscale conducting nanoroad.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 In this study, we use first-principles calculations within density functional theory (DFT) 70 to investigate the energetics of hydrogenation on the MoS 2 monolayer and the resulting change in electronic properties with aim to explore the possibility of the surface metallization and the construction of conducting channels. Clearly the motivation to hydrogenate MoS 2 here is in stark contrast to that to hydrogenate graphene: hydrogenating graphene causes its band gap openinga metal to insulator transition-which can be used to create 5 insulating ribbons or clusters on graphene. 20,21 Our ballistic conductance calculation shows that hydrogenation-induced metallization is viable on MoS 2 monolayer and strip-patterned hydrogenation can generate a nanoscale conducting nanoroad.…”
Section: Introductionmentioning
confidence: 99%
“…While the amount of H adsorption on MoS 2 can be expressed as H x MoS 2 (x<1), 18 the accurate value of x on the surface is still unknown. Although we have shown that a small amount of defects like H vacancies will not degrade the metallic behavior of the hydrogenated MoS 2 strip (see the Supporting Information), the ability to control H coverage is still a critical 5 issue in any device applications. Previous studies have shown that Ni, Pt and Co-promoted MoS 2 19,38,39 has a much larger uptake of H compared with unpromoted MoS 2 .…”
Section: Dihydrogenated Mosmentioning
confidence: 99%
See 1 more Smart Citation
“…Pump-probe spectroscopy in lightly photoexcited SrTiO 3 suggested that itinerant electron polarons are the origin of diffusive lattice distortions 14 . However, the large-polaron model cannot explain the ingap bulk states in the conductive phase revealed in photoemission spectroscopy [20][21][22][23] . Instead, these highly localized states are attributable to small polarons trapped in bulk sites.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, small polarons form highly localized in-gap states and can hop to adjacent lattice sites when thermally activated 10 . Experimental information on the role of polarons in SrTiO 3 is abundant, yet controversial [11][12][13][14][15][16][17][18][19][20][21][22][23][24] . The key question is whether it is a large or a small polaron that is formed.…”
Section: Introductionmentioning
confidence: 99%